Affective Infrastructures of Re-emergence? Exploring Modalities of Heritage Practices in Nantes. (3rd May 2020) - Knudsen, Britta Timm; Kølvraa, Christoffer
ABSTRACT: The French city of Nantes has been heralded for both its creative and complex engagements with the dark heritage of its history as France's main slave port. In this article we examine the ways in which the colonial heritage has been dealt with in Nantes, arguing that we find here various processes and initiatives which can be understood as expressing or combining what we suggest are four main modes of colonial heritage practice: Repression, Removal, Reframing and Re-emergence. We discuss how the city authorities and local organizations with a focus on colonial heritage have ended the silent repression of the city's slave trading heritage, and to some extent entirely reframed the city as a center of avant-garde art and culture, e.g., through the 2012 construction of Memorial to the Abolition of Slavery. Finally, we critically analyze the domesticating effect of this reframing as well as practices of removal which, by contrast, have been used to reintroduce decolonial antagonism and oppositional struggle into the public space in Nantes. Finally we investigate whether street performances of Royal de Luxe might hold what we term potential for re-emergence; a heritage practice entailing both a reemergent aesthetics able to engage the audience at a bodily and affective level, a re-emergent history able to both articulate the past and energize contemporary struggles, and the re-emergence of a broader field of voices and subjects.